640PExpression profile of EPHB3 and its prognostic significance in colorectal cancer progression (Running head: Prognostic value of EPHB3 in colorectal cancers). (1st October 2019) - Jang, B; Kim, H
Abstract: Background: A tumour suppressive role for EPHB receptors in various malignancies has been described, however their expression profile and prognostic significance in human colorectal cancers (CRCs) remain unclear. In this study, we aimed to investigate the expression profile of EPHB3 during CRC progression and determined its prognostic impact in a large cohort of CRC samples. Methods: We examined the EPHB3 mRNA levels by real time PCR with fresh frozen CRC samples and evaluated protein expression by immunohistochemistry with tissue microarrays containing various benign tumours and 610 CRC samples. AOM-DSS induced colitis model was used to investigate the EPHB3 expression profile during the colitis-associated carcinogenesis. Results: EPHB3 expression was upregulated in CRCs than in normal colonic mucosa, and showed positive correlations with intestinal stem cell (ISC) markers (EPHB2, OLFM4, LRIG1) and CD44, a candidate cancer stem cell marker. EPHB3 positivity was observed in 24% of 610 CRCs and showed negative correlations with differentiation, lympho-vascular invasions and TNM stages. EPHB3 expression significantly declined during adenoma-carcinoma transition and invasion into deeper layers. In particular, a substantial reduction of EPHB3 was observed in the budding cancer cells at the invasive fronts. In AOM-DSS induced colitis-associated colon cancer model, EPHB3 expression increased along with tumor development. Notably, EPHB3 was positively associated with microsatellite instability (MSI) phenotype but was not associated with CpG island methylator phenotype, KRAS and BRAF mutations. Furthermore, EPHB3 positivity was a prognostic marker for better clinical outcomes in CRC patients. Conclusions: EPHB3 was upregulated in CRCs and showed positive correlations with candidate cancer stem cell marker CD44. EPHB3 expression decreased during adenoma-carcinoma transition and particularly in the budding cancer cells at the invasive fronts. EPHB3 positivity was associated with MSI phenotype and demonstrated to be a good prognostic marker in CRCs. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.